Pengaruh Pelatihan Pengembangan Karyawan Dan Kompetensi Karyawan Terhadap Produktivitas Kerja Pada Karyawan Divisi Operasional Kapal PT. Suntraco Intim Transport - Alberto Charles Berek; Indriana Kristiawati; Meyti Hanna Ester Kalangi (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
Introduction: The purpose of this study is to analyze the impact of training, employee development and employee competence on employee productivity in the Operational Division of Ship Pt. Suntraco Intim Transport. Research Methodology: The research method used is quantitative descriptive. The sampling technique used is saturated samples so from a population samples as many as 30 respondents, data collection methods used are observation, lifting, and library. The analytical tools used in this study are SPSS software version 23. The data analysis techniques used are double linear regression, t test, F test and determination coefficient. Research results: From the results of the analysis using the test T, analysis F testing the hypothesis at the level of confidence α = 5%, the t count value of 2.565 > t table 2.042 and the significant value is of 0.016 < 0.05 then it can be concluded that the Employee Training variable influences on the Work Productivity Employees operational division of the ship PT. Suntraco Intim Transport, Surabaya. for the hypothesis number two obtained a counting t value of 2.183 > t Table 2.042, and the significance value is 0.038 < 0.05, then it could be concluted that the employee development variable has a significant influence on the labour productivity of the employees of the operational divisions of the ships of PT. Sunraco intim transport, Surabaya. for the three hypotheses the counting value of the number three is 2. 183 > T table 2,042 and its significance is 0.010 < 0,05 then it was possible to conclude that the staff competence significantly influenced on the performance of the work of the staff of the PT. Suntraco Intim Transport, Surabaya